BIG DATA FOR CLASSIFICATION OF COMMUNITY COMPLAINTS AGAINST PUBLIC SERVICES ON TWITTER - Muqorobin Muqorobin; Zul Hisyam; Arief Setyanto (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
..................................... .....................................